Pengembangan Game Edukasi Interaktif Perhitungan Waris dalam Pendidikan Agama Islam Menggunakan Scratch - Ali, Muttaqin Kholis; Ali, Al Muhtadibillah; Hasanah, Arrahmil (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to develop and evaluate the effectiveness of interactive educational games in learning inheritance calculation material in Islamic Religious Education subjects using the Scratch platform. The research method used is Research and Development (R&D) with the ADDIE model. Game development involves the integration of learning content, gamification elements, and adaptive systems. Validation was carried out by media and material experts, while the trial involved 60 high school students. The results showed a very high level of feasibility from media experts (96%) and material experts (97%). The trial on students showed a significant increase in material comprehension (p < 0.001) and learning motivation. Educational games have proven to be effective in improving students' knowledge transfer skills, long-term retention, and critical thinking skills. Qualitative analysis revealed a positive impact on the social-emotional aspects of learning. This research makes a significant contribution to the development of innovative learning media for complex materials in Islamic Religious Education and opens opportunities for further research in the integration of game technology in religious education